Removal of nitrophenols from water using cellulose derived nitrogen doped graphitic carbon material containing titanium dioxide. (19th May 2019) - RanguMagar, Ambar B.; Chhetri, Bijay P.; Parnell, Charlette M.; Parameswaran-Thankam, Anil; Watanabe, Fumiya; Mustafa, Thikra; Biris, Alexandru S.; Ghosh, Anindya
ABSTRACT: Nitrophenols (NPs) and their derivatives are highly toxic, mutagenic and bio-refractory pollutants commonly present in natural water resources and industrial wastewater. To remove NPs from water, N-doped graphitic carbon (NGC) and NGC adsorbent containing titanium dioxide (NGC–TiO2 ) were synthesized by pyrolysis of microcrystalline cellulose and dopamine mixture, and the mixture along with TiO2 at 500°C, respectively. NCG-TiO2 was thoroughly characterized using various analytical techniques. NP adsorption on the NGC–TiO2 adsorbent surface was studied by varying the pH, initial concentration of NP, and adsorbent dose. The results showed that the most efficient adsorption was achieved at pH 3. After 4 h sonication at pH 3, 80% 4-NP adsorption was achieved using NGC–TiO2 compared to 74% with NGC adsorbent. The percentage removal of 4-NP was higher than 3-NP which was also higher than 2, 4-DNP using NGC–TiO2 . 4-NP adsorption best fitted to the Langmuir isotherm plot with R 2 value of 0.9981 and adsorption capacity of 52.91 mg g −1 . The adsorption process of NP was found to follow a pseudo-second-order kinetic model. The rate constant value for the adsorption of 10 −4 M 4-NP at pH 3 using 10 mg of NGC–TiO2 adsorbent was found to be 3.76 × 10 −5 g.mg −1 .min −1